Composition of antifungal volatile organic compounds in Sextonia rubra fruit by molecular networks - Levasseur, Marceau; Santerre, Cyrille; Segret, Juliette; Elie, Nicolas; Genty, Christophe; Estevez, Yannick; Amusant, Nadine; Houël, Emeline; Eparvier, Véronique; Touboul, David (Comptes Rendus. Chimie)
Sextonia rubra is a tropical tree exploited for its durable wood. Hydrodistillation of its fruit was performed for the first time and the resulting hydrolate was analyzed by headspace-solid phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) together with the dried fruit. Data analysis was performed by conventional methods and by molecular networks using MetGem software. Our methodology proved to be efficient to annotate the compounds detected complementary to the use of MassHunter Unknown Analysis.Hydrolate and dried fruit both displayed a rich and diverse HS-SPME-GC-MS sesquiterpenic profile, alongside with moderate antimicrobial activity towards the filamentous fungus Tricophyton rubrum for the hydrolate.